2009
DOI: 10.1074/jbc.m900019200
|View full text |Cite
|
Sign up to set email alerts
|

TATA-binding Protein and Transcription Factor IIB Induce Transcript Slipping during Early Transcription by RNA Polymerase II

Abstract: To better understand the mechanism of steps in early transcription by RNA polymerase II (pol II), we investigated the molecular determinants of transcript slipping within complexes assembled on promoters containing a pre-melted transcription bubble from ؊9 to ؉3. Transcript slippage occurs when an RNA transcript contains a repetitive sequence that allows the transcript to slip back and pair with the template strand of the DNA at a new register before transcription continues. We established the contributions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
2
9
1
Order By: Relevance
“…In addition, the E51R:R66E double mutant did not produce the 11-nt transcript in the presence of CpA (lane 10). Like results reported recently with a similar system, slippage was greatly reduced by priming with the CpA dinucleotide (44). We conclude that the defect in transcriptional activity of mutations in residues Glu-51 and Arg-66 is independent of the ability to recognize the start site.…”
Section: Change-of-charge Mutants In Minimal Promotersupporting
confidence: 68%
See 1 more Smart Citation
“…In addition, the E51R:R66E double mutant did not produce the 11-nt transcript in the presence of CpA (lane 10). Like results reported recently with a similar system, slippage was greatly reduced by priming with the CpA dinucleotide (44). We conclude that the defect in transcriptional activity of mutations in residues Glu-51 and Arg-66 is independent of the ability to recognize the start site.…”
Section: Change-of-charge Mutants In Minimal Promotersupporting
confidence: 68%
“…The major transcript from this promoter is a 10-nt G-less RNA. Longer and shorter minor transcripts are also present, indicating the "slippage" of the transcription complex that has been documented by others (43,44) and is dependent upon the presence of TBP and TFIIB (44).…”
Section: Resultsmentioning
confidence: 94%
“…Candidate macromolecules include RNA polymerase binding factors. Interestingly, recent studies revealed that transcript slippage during initiation by human RNA polymerase II can be induced by the TATA-binding protein and transcription factor TFIIB [9 •• ]. Other potential signals are factors that control transcription pausing, particularly during transcription elongation.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism apparently involves one or more rounds of a one-base upstream shift of the transcript so that the same nucleotide in the template specifies multiple residues in the transcript [7,8]. It has also been shown that reiterative transcription can occur within dinucleotide [9 •• ,10] and trinucleotide [11] repeat sequences in the template, apparently via two-base and three-base upstream shifts of the transcript, respectively. Reiterative transcription can occur during initiation, elongation, or termination and result in transcripts that are immediately released from the transcription complex [12,13 •• ] or are extended by normal elongation after a switch to nonreiterative nucleotide addition [14,15 •• ].…”
Section: Introductionmentioning
confidence: 99%
“…16 Several studies suggest a role for TFIIB in promoter escape by pol II. 11,14,17,18 In early pol II transcription, short DNA-RNA hybrids are unstable and are transiently ejected from the enzyme (abortive transcription initiation). It has been proposed that the TFIIB B-finger/B-reader loop stabilizes the short RNA transcripts with pol II until the growing RNA reaches seven nucleotides and TFIIB is triggered to release from the initiation apparatus as pol II enters the productive elongation complex (promoter escape).…”
mentioning
confidence: 99%